Preparation of Clove Essential Oil-Chitosan Composite Film and Its Application in Rice Preservation - Qian HAN; Si CHEN; Xiaoling HUANG; Shihui LIU; Xiuying LIU; Pingping WANG; Wei ZHANG; Zaixi SHU; Lijie ZHU (Shipin gongye ke-ji)
Objective: To investigate the effect of adding clove oil (CEO) on the properties of CEO/chitosan (CS) composite films, including optical and mechanical properties. Additionally, it explored the effectiveness of these films with varying amounts of CEO in maintaining the freshness of cooked rice under room temperature. Methods: Composite films were developed using a chitosan matrix and blended with varying CEO contents (0%, 0.5%, 1%, 1.5%, 2%). Their physicochemical properties and internal structure were characterized. These films were applied to cooked rice, and the total colony count and sensory evaluation indicators were monitored during the rice's storage period. Results: The composite film with a 1.5% addition of CEO exhibited the optimum overall performance, with the water vapor permeability of 3.80×10−3 g/(h·m·kPa) and the elongation at break of 40.33%. Additionally, the film efficiently decreased the total colony count of rice during storage. Compared with the control (group CK and PE), the rice treated with the film could effectively extending shelf life by an additional 2 d. Conclusion: Adding CEO was able to enhance the properties of chitosan composite films. The addition content of 1.5% efficiently maintained the quality of cooked rice during storage. This study can provide a reference for the application of CEO in the preservation of ready-to-eat rice.